Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Dinas Perhubungan Kabupaten Penajam Paser Utara - St. Aisyah; St Rukaiyah (Jurnal Online Manajemen ELPEI, 2026)
This study aims to identify and analyze (1) the effect of work discipline on employee performance at the Transportation Office of Penajam Paser Utara Regency, (2) the effect of the work environment on employee performance at the Transportation Office of Penajam Paser Utara Regency, and (3) the simultaneous effect of work discipline and work environment on employee performance at the same institution. The research employed a quantitative correlational approach, with data collected through questionnaires. The results show that work discipline has a positive and significant effect on improving employee performance. Compliance with rules, punctuality, and a high level of responsibility form the foundation of work behavior that directly contributes to the achievement of optimal work outcomes. The work environment also has a positive and significant effect on performance. Non-physical aspects, particularly supervisor support and harmonious working relationships, are the main driving forces, while improvements in the physical environment are still necessary to support productivity more evenly. Work discipline and the work environment together exert a very strong and dominant influence on employee performance. These two variables create a synergistic effect, where work discipline builds behavioral structure and consistency, while a supportive work environment provides motivational and relational context that strengthens and optimizes the contribution of discipline toward performance achievement.